Op Pinksterkamp te Beekbergen. Henk tweede, Mien derde van links. Origineel in Sneevliet-archief, album 8 (1934)
Op Pinksterkamp te Beekbergen. Henk tweede, Mien derde van links. Origineel in Sneevliet-archief, album 8.